2017
DOI: 10.1038/ncomms14634
|View full text |Cite
|
Sign up to set email alerts
|

MICU1 drives glycolysis and chemoresistance in ovarian cancer

Abstract: Cancer cells actively promote aerobic glycolysis to sustain their metabolic requirements through mechanisms not always clear. Here, we demonstrate that the gatekeeper of mitochondrial Ca2+ uptake, Mitochondrial Calcium Uptake 1 (MICU1/CBARA1) drives aerobic glycolysis in ovarian cancer. We show that MICU1 is overexpressed in a panel of ovarian cancer cell lines and that MICU1 overexpression correlates with poor overall survival (OS). Silencing MICU1 in vitro increases oxygen consumption, decreases lactate prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
129
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(132 citation statements)
references
References 71 publications
3
129
0
Order By: Relevance
“…Despite effectiveness of the first-line carboplatin and paclitaxel regimen, the majority of ovarian cancer patients die because they develop chemoresistant disease (36,37). Numerous receptors and pathways are known to be critical in ovarian cancer chemoresistance (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51), but no targeted agent has been shown to enhance sensitivity to both carboplatin and paclitaxel. Here, we present several lines of evidence that AXL has a critical role in resistance to paclitaxel and carboplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Despite effectiveness of the first-line carboplatin and paclitaxel regimen, the majority of ovarian cancer patients die because they develop chemoresistant disease (36,37). Numerous receptors and pathways are known to be critical in ovarian cancer chemoresistance (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51), but no targeted agent has been shown to enhance sensitivity to both carboplatin and paclitaxel. Here, we present several lines of evidence that AXL has a critical role in resistance to paclitaxel and carboplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MICU1 appears to be a favorable prognostic marker in renal cancer (https://www.proteinatlas.org/ENSG00000107745-MICU1/pathology). In contrast, high MICU1 levels confer chemoresistance to ovarian cancer cells (Chakraborty et al , ), and MICU1 downregulation has been associated with a higher sensitivity to apoptotic stress and impaired endothelial cell migration (Mallilankaraman et al , ). However, an accelerated proliferation of MICU1 ‐knockdown hepatocytes has been recently observed following treatment with NIM811 (Antony et al , ), which is an inhibitor of the mitochondrial permeability transition pore (mPTP), the channel responsible for the initiation of mitochondrial cell death programs (Bonora et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Drugs such as arsenic trioxide (As 2 O 3 ) (Gunes et al 2009) and gamitrinib (Park et al 2014) were suggested to promote ER Ca 2+ release during short-term exposure. Short-term exposure of cancer cells to cisplatin (Shen et al 2016;Chakraborty et al 2017), doxorubicin (Giorgi et al 2015a), or photodynamic therapy (PDT) (Giorgi et al 2015b), may enhance ER-mitochondria Ca 2+ transfer in some models. Examples of the remodeling of Ca 2+ signaling with longer term drug treatments include altered store-operated Ca 2+ entry (SOCE) as a result of treatment with 5-Fluorouracil (Kondratska et al 2014;Tang et al 2017), gemcitabine (Kondratska et al 2014) or cisplatin (Schmidt et al 2014).…”
Section: Discussionmentioning
confidence: 99%